Negative elongation factor is essential for endometrial function. Issue 2 (17th October 2018) - Hewitt, Sylvia C.; Li, Rong; Adams, Nyssa; Winuthayanon, Wipawee; Hamilton, Katherine J.; Donoghue, Lauren J.; Lierz, Sydney L.; Garcia, Marleny; Lydon, John P.; DeMayo, Francesco J.; Adelman, Karen; Korach, Kenneth S.
ABSTRACT: Pausing of RNA polymerase II (Pol II) during early transcription, mediated by the negative elongation factor (NELF) complex, allows cells to coordinate and appropriately respond to signals by modulating the rate of transcriptional pause release. Promoter proximal enrichment of Pol II occurs at uterine genes relevant to reproductive biology; thus, we hypothesized that pausing might impact endometrial response by coordinating hormonal signals involved in establishing and maintaining pregnancy. We deleted the NELF‐B subunit in the mouse uterus using PgrCre (NELF‐B UtcKO). Resulting females were infertile. Uterine response to the initial decidual stimulus of NELF‐B UtcKO was similar to that of control mice; however, subsequent full decidual response was not observed. Cultured NELF‐B UtcKO stromal cells exhibited perturbances in extracellular matrix components and also expressed elevated levels of the decidual prolactin Prl8a2, as well as altered levels of transcripts encoding enzymes involved in prostaglandin synthesis and metabolism. Because endometrial stromal cell decidualization is also critical to human reproductive health and fertility, we used small interfering to suppress NELF‐B or NELF‐E subunits in cultured human endometrial stromal cells, which inhibited decidualization, as reflected by the impaired induction of decidual markers PRL and IGFBP1 . Overall, our study indicates NELF‐mediated pausing is essential to coordinate endometrial responses and that disruption impairs uterine decidual development during pregnancy.—Hewitt, S. C., Li, R., Adams, N., Winuthayanon, W., Hamilton, K. J., Donoghue, L. J., Lierz, S. L., Garcia, M., Lydon, J. P., DeMayo, F. J., Adelman, K., Korach, K. S. Negative elongation factor is essential for endometrial function. FASEB J. 33, 3010–3023 (2019). www.fasebj.org